Synthesis, antimicrobial activity, computational and modeling studies of some new organotellurium compounds containing azo moities - Al-Masoudi, Wasfi Aboud; Al-Asadi, Rafid Hmedan; Othman, Rasha Munther; Al‐Masoudi, Najim Aboud (European Journal of Chemistry, 2015)
A new series of organonotellurium compounds containing azo groups were prepared by new and convenient methods. Reaction of 1-(4-mercuric chloride-2,3-dichlorophenyl)-2-chloro diazine (4) with 8-hydroxyquinoline (5) gave the new organomercury compound 6 in good yield. Telluratio of compound 6 with tellurium tetrabromide in 1:1 and 1:2 mole ratio gave the o-tellurated azo compounds ArTeBr3 (7) and Ar2TeBr2 (9), respectively. Reduction of both ArTeBr3 and Ar2TeBr2 by hydrazine hydrate gave the ditelluride 8, and telluride 10, respectively. The synthesized compounds were screened for their antibacterial activity against Staphylococcus aureus, Escherichia coli, Bacillus subtilis, Klebsiella pneumonia, Salmonella spp., Streptococcus spp. and Bacillus cereus. Additionally, the prepared compounds were tested for antifungal activity against Candida sp., Aspergillus multi and Aspergillus niger. All compounds exhibited good antibacterial and antifungal activity. Computational study of the new compounds was calculated using Gaussian 09 program package. Molecular modeling studies were performed and showed hydrogen binding and hydrophobic interactions.